Markers of Hemostatic Activation in Affected Coronary Arteries during Angioplasty - Shammas, Nicolas W; Cunningham, Michael J; Pomearntz, Richard M; Francis, Charles W (Thrombosis and Haemostasis, 1994)
To characterize the extent of early activation of the hemostatic system following angioplasty, we obtained blood samples from the involved coronary artery of 11 stable angina patients during the procedure and measured sensitive markers of thrombin formation (fibrino-peptide A, prothrombin fragment 1.2, and soluble fibrin) and of platelet activation ((3-thromboglobulin). Levels of hemostatic markers in venous blood obtained from 14 young individuals with low pretest probability for coronary artery disease were not significantly different from levels in venous blood or intracoronary samples obtained prior to angioplasty. Also, there was no translesional (proximal and distal to the lesion) gradient in any of the hemostatic markers before or after angioplasty in samples obtained between 18 and 21 min from the onset of the first balloon inflation. Furthermore, no significant difference was noted between angioplasty and postangioplasty intracoronary concentrations. We conclude that intracoronary hemostatic activation does not occur in the majority of patients during and immediately following coronary angioplasty when high doses of heparin and aspirin are administered.